Systemic and topical antibiotics for chronic rhinosinusitis - Head, Karen; Chong, Lee Yee; Piromchai, Patorn; Hopkins, Claire; Philpott, Carl; Schilder, Anne G M; Burton, Martin J (Cochrane database of systematic reviews, 2016)
This review is one of six looking at the primary medical management options for patients with chronic rhinosinusitis.Chronic rhinosinusitis is common and is characterised by inflammation of the lining of the nose and paranasal sinuses leading to nasal blockage, nasal discharge, facial pressure/pain and loss of sense of smell. The condition can occur with or without nasal polyps. Systemic and topical antibiotics are used with the aim of eliminating infection in the short term (and some to reduce inflammation in the long term), in order to normalise nasal mucus and improve symptoms. To assess the effects of systemic and topical antibiotics in people with chronic rhinosinusitis. The Cochrane ENT Information Specialist searched the Cochrane ENT Trials Register; CENTRAL (2015, Issue 8); MEDLINE; EMBASE; ClinicalTrials.gov; ICTRP and additional sources for published and unpublished trials. The date of the search was 29 September 2015. Randomised controlled trials (RCTs) with a follow-up period of at least three months comparing systemic or topical antibiotic treatment to (a) placebo or (b) no treatment or (c) other pharmacological interventions. We used the standard methodological procedures expected by Cochrane. Our primary outcomes were disease-specific health-related quality of life (HRQL), patient-reported disease severity and the commonest adverse event - gastrointestinal disturbance. Secondary outcomes included general HRQL, endoscopic nasal polyp score, computerised tomography (CT) scan score and the adverse events of suspected allergic reaction (rash or skin irritation) and anaphylaxis or other very serious reactions. We used GRADE to assess the quality of the evidence for each outcome; this is indicated in italics. We included five RCTs (293 participants), all of which compared systemic antibiotics with placebo or another pharmacological intervention.The varying study characteristics made comparison difficult. Four studies recruited only adults and one only children. Three used macrolide, one tetracycline and one a cephalosporin-type antibiotic. Three recruited only patients with chronic rhinosinusitis without nasal polyps, one recruited patients with chronic rhinosinusitis with nasal polyps and one had a mixed population. Three followed up patients for 10 to 12 weeks after treatment had finished. Systemic antibiotics versus placebo Three studies compared antibiotics with placebo (176 participants).One study (64 participants, without polyps) reported disease-specific HRQL using the SNOT-20 (0 to 5, 0 = best quality of life). At the end of treatment (three months) the SNOT-20 score was lower in the group receiving macrolide antibiotics than the placebo group (mean difference (MD) -0.54 points, 95% confidence interval (CI) -0.98 to -0.10), corresponding to a moderate effect size favouring antibiotics (moderate quality evidence). Three months after treatment, it is uncertain if there was a difference between groups.One study (33 participants, with polyps) provided information on gastrointestinal disturbances and suspected allergic reaction (rash or skin irritation) after a short course of tetracycline antibiotic compared with placebo. We are very uncertain if antibiotics were associated with an increase in gastrointestinal disturbances (risk ratio (RR) 1.36, 95% CI 0.22 to 8.50) or skin irritation (RR 6.67, 95% CI 0.34 to 128.86) (very low quality evidence). Systemic antibiotics plus saline irrigation and intranasal corticosteroids versus placebo plus saline irrigation and intranasal corticosteroids One study (60 participants, some with and some without polyps) compared a three-month course of macrolide antibiotic with placebo; all participants also used saline irrigation and 70% used intranasal corticosteroids. Disease-specific HRQL was reported using SNOT-22 (0 to 110, 0 = best quality of life). Data were difficult to interpret (highly skewed and baseline imbalances) and it is unclear if there was an important difference at any time point (low quality evidence). To assess patient-reported disease severity participants rated the effect of treatment on a five-point scale (-2 for "desperately worse" to 2 for "cured") at the end of treatment (three months). For improvement in symptoms there was no difference between the antibiotics and placebo groups; the RR was 1.50 (95% CI 0.81 to 2.79; very low quality evidence), although there were also slightly more people who felt worse after treatment in the antibiotics group. There was no demonstrable difference in the rate of gastrointestinal disturbances between the groups (RR 1.07, 95% CI 0.16 to 7.10). General HRQL was measured using the SF-36. The authors stated that there was no difference between groups at the end of treatment (12 weeks) or two weeks later. Systemic antibiotics versus intranasal corticosteroids One study (43 participants, without polyps) compared a three-month course of macrolide antibiotic with intranasal corticosteroids. Patient-reported disease severity was assessed using a composite symptom score (0 to 40; 0 = no symptoms). It is very uncertain if there was a difference as patient-reported disease severity was similar between groups (MD -0.32, 95% CI -2.11 to 1.47; low quality evidence). Systemic antibiotics versus oral corticosteroids One study (28 participants, with polyps) compared a short course of tetracycline antibiotic (unclear duration, ˜20 days) with a 20-day course of oral corticosteroids. We were unable to extract data on any of the primary efficacy outcomes. It is uncertain if there was a difference ingastrointestinal disturbances (RR 1.00, 95% CI 0.16 to 6.14) or skin irritation (RR 2.00, 95% CI 0.20 to 19.62) as the results for these outcomes were similar between groups (very low quality evidence). We found very little evidence that systemic antibiotics are effective in patients with chronic rhinosinusitis. We did find moderate quality evidence of a modest improvement in disease-specific quality of life in adults with chronic rhinosinusitis without polyps receiving three months of a macrolide antibiotic. The size of improvement was moderate (0.5 points on a five-point scale) and only seen at the end of the three-month treatment; by three months later no difference was found.Despite a general understanding that antibiotics can be associated with adverse effects, including gastrointestinal disturbances, the results in this review were very uncertain because the studies were small and few events were reported.No RCTs of topical antibiotics met the inclusion criteria.More research in this area, particularly evaluating longer-term outcomes and adverse effects, is required.